2009
DOI: 10.1016/j.ijadhadh.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adhesive bond line thickness on joint strength

Abstract: WOSInternational audienceWhile the geometry of aerospace assemblies is carefully controlled, for many industrial applications such as marine structures bond line thickness can vary significantly. In this study epoxy adhesive joints of different thicknesses between aluminium substrates have been characterized using physico-chemical analyses (differential scanning calorimetry, DSC; dynamic mechanical analysis, DMA; spectroscopy), nano-indentation and mechanical testing. Thermal analyses indicated no influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(51 citation statements)
references
References 36 publications
3
47
0
1
Order By: Relevance
“…However, for the joint with the scarf angle θ ¼90°, where pure tensile stress occurs at the interface, the ultimate tensile loading F u of DSJ is just governed by the cohesive strength in mode I (σ u,I ) of the adhesive. Davies et al [21] reported that a decrease of tension/shear loads as the adhesive thickness increases, which coincides with the results obtained in the present study (as shown in Fig. 7).…”
Section: Effect Of Geometrysupporting
confidence: 93%
“…However, for the joint with the scarf angle θ ¼90°, where pure tensile stress occurs at the interface, the ultimate tensile loading F u of DSJ is just governed by the cohesive strength in mode I (σ u,I ) of the adhesive. Davies et al [21] reported that a decrease of tension/shear loads as the adhesive thickness increases, which coincides with the results obtained in the present study (as shown in Fig. 7).…”
Section: Effect Of Geometrysupporting
confidence: 93%
“…Davies et al [20] studied the nano-mechanical behavior of epoxy adhesive joints with varying thicknesses that were bonded to aluminum substrates. They used the nanoindentation technique to understand different aspects associated with the joint interphase such as modulus of the joints and substrate/adhesive.…”
Section: Investigations On Epoxy Based Coatingsmentioning
confidence: 99%
“…In order to address properly non linearity and failure of these materials, which were clearly not obtained with the Iosipescu test, shear tests using the modified Arcan fixture have been evaluated, Figure 6. The Arcan test was initially developed [8] to produce uniform plane stress and a modified 100 Advances in Experimental Mechanics VII version has been used recently, associated with image analysis, to characterize bonded joints [9]. Different geometries of samples have been investigated and finally 0.5*7,6*66mm 3 specimen bonded on aluminium support have been selected in order to minimize the effect due to the appearance of normal stress.…”
Section: Shear Testmentioning
confidence: 99%